Optimizing service caching in smart buildings: a dynamic approach for responsive IoT and edge computing integration in smart cities - Harrabi, Mokhtar; Hamdi, Abdelaziz; Bel Hadj Tahar, Jamel (Frontiers in Communications and Networks, 2024)
This paper introduces a novel approach for optimizing service caching in smart buildings through the integration of Internet of Things (IoT) and edge computing technologies. Traditional cloud-based solutions often experience high latency and resource consumption, limiting the performance of smart city applications. To address these challenges, a dynamic crowdsourcing and caching algorithm is proposed, leveraging IoT gateways and edge servers to reduce latency and improve responsiveness. The algorithm prioritizes services for caching based on a newly developed efficiency metric, which accounts for cloud and edge-computed response times, memory usage, and service popularity. Experimental results demonstrate a reduction in average response time (ART) by up to 25% and a 15% improvement in resource utilization compared to traditional methods. These results highlight the approach's suitability for resource-constrained environments, making it a promising solution for smart city infrastructures and providing a basis for further advancements in edge-based service optimization.